JUDGES' CODE OF ETHICS: FOUNDATION FOR MAINTAINING INTEGRITY AND ACCOUNTABILITY - Andri Nurwandri; Astri Anggraini; Armi Puspita Zaini (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Judges are members of the Catur Wangsa Law Enforcement in Indonesia. The integrity and accountability of a judge becomes an actor in determining public trust in the justice system. -moral and ethical values. The judge's code of ethics has been compiled to guide the behavior and moral standards that must be adhered to by judges. This research uses a qualitative research method with a descriptive-analytic approach which aims to provide an in-depth understanding regarding the basic code of ethics for judges in maintaining judicial integrity and accountability. The main sources for this research come from related literature, including books, scientific journals and official documents which discuss judges' codes of ethics, integrity values and accountability principles in the judicial context. used in this research consists of primary data and secondary data. The definition of a judge's code of ethics is a concrete expression of ethics, morality and religion. The judge's code of ethics is an important basis for maintaining integrity and responsibility. You must be able to face challenges and be balanced, taking full responsibility and responding to your challenges. Conscience, ethical values of society and SWT Allah SWT, and because being a judge is a profession, there is a need for a code of ethics or professional code.